Casa Pueblo A Puerto Rican Model of Self-Governance - Massol González, Alexis (Lever Press, 2022)
As a community-based organization in the mountains of south-central Puerto Rico, Casa Pueblo implements alternatives to extractive capitalism that do not rely on governments or distant non-profits. In this book, Alexis Massol González, Casa Pueblo's founder, reflects on its extraordinary forty-year history of experiments with community self-governance. Massol-González received the prestigious Goldman Prize (popularly known as the Green Nobel) for the organization's initiatives to protect the environment, affirm cultural and human values, and create sustainable economic alternatives. This collective translation was undertaken in the spirit of the organization and offers a chronological account of Casa Pueblo's evolution from a small group of concerned citizens to an internationally recognized model for activism.